2021
DOI: 10.1093/rheumatology/keab806
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA genetic variants are associated with systemic lupus erythematosus susceptibility, glucocorticoids efficacy and prognosis

Abstract: Objective To investigate the associations of mitochondrial DNA (mtDNA) genetic variants with SLE susceptibility, glucocorticoid (GC) efficacy and prognosis. Methods Our study was done in two stages. First, we performed whole mitochondrial genome sequencing in 100 patients and 100 controls to initially screen potential mtDNA variants associated with disease and GC efficacy. Then, we validated the results in an independent set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It was reported that mitochondrial genetic alterations are related to the occurrence of SLE, [ 84 ] and that novel mtDNA genetic variants are associated with SLE susceptibility and prognosis. [ 85 ] mtDNA deposits have been found in the NETs of LN kidney biopsy specimens. [ 86 ] Moreover, SLE patients have higher levels of anti-mtDNA antibodies than healthy individuals, which is associated with the disease activity index in patients with LN.…”
Section: Mtdna-cgas-sting Pathway In Kidney Diseasementioning
confidence: 99%
“…It was reported that mitochondrial genetic alterations are related to the occurrence of SLE, [ 84 ] and that novel mtDNA genetic variants are associated with SLE susceptibility and prognosis. [ 85 ] mtDNA deposits have been found in the NETs of LN kidney biopsy specimens. [ 86 ] Moreover, SLE patients have higher levels of anti-mtDNA antibodies than healthy individuals, which is associated with the disease activity index in patients with LN.…”
Section: Mtdna-cgas-sting Pathway In Kidney Diseasementioning
confidence: 99%